Waiting to be heard : a memoir - Knox, Amanda (HarperCollins, 2013)
Amanda Knox's account of her hard-fought battle to overcome injustice and win the freedom she deserved after spending four years in prison for the murder of Meredith Kercher in Perugia, Italy.